A Model of Education and Struggle of Social Status of Rural Women in Practical Politics at Bali Province - I Nyoman Jampel; I Wayan Lasmawan (Jurnal Pendidikan Indonesia, 2019)
The targets of this study were: find out a model of the political education for rural women in the province of Bali based on the wisdom of local cultural values. For the first year (2012), the product of this study consisted of: the constellation of practical politics of Bali woman profile, the draft of a model-based political education gender equality, gender mainstreaming draft models for Bali women in the political, scientific articles published in accredited journals. Overall the research data was analyzed using descriptive qualitative analysis techniques and statistical analysis to test the effectiveness of political education model for rural women in Bali. Based on the overall research process, it gained some critical issues related to gender mainstreaming in politics at the indigenous Bali as a conclusion of this study, namely: 1) the pattern of communication and daily activity of customary village communities, the role of women’s political participation tends to be low Bali. It is mostly contributed by the application of patriarchal ideology, an ideology of kinship that put men as central ownership of the rights and obligations of the public at the level of everyday life, so that the position and status of women are subordinated. (2) The status and role of women in politics so marginalized activity, except in some aspects that still exist within the family environment, as can be seen in a symbolic meaning for the name pungkusan each nuclear family. (3) Climate and communication patterns of family life, customary village and administrative village, school does not support the process of political education for indigenous Balinese women to achieve improvement. (4) Customary village as the as the highest symbolism level of the indigenous Balinese, structurally, yet real activity in relation to the political education of the girls. (5) The process of the formation of Indonesian civil society, in conjunction with the purpose and characteristics of the indigenous Balinese customary village turned out to be quite relevant in creating a climate of gender equality